2014
DOI: 10.1136/gutjnl-2013-305827
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effects of low-dose enteric-coated aspirin tablets on the development of colorectal tumours in Asian patients: a randomised trial

Abstract: Low-dose, enteric-coated aspirin tablets reduced colorectal tumour recurrence in an Asian population. The results are consistent with those obtained from other randomised controlled trials in Western countries. THE CLINICAL TRIAL REGISTRY WEBSITE AND THE CLINICAL TRIAL NUMBER: http://www.umin.ac.jp (number UMIN000000697).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 28 publications
4
101
2
Order By: Relevance
“…Although the dose of aspirin and other aspects of these RCTs varied, the efficacy of aspirin was essentially consistent, providing a modest 17-35% reduction in risk of recurrent adenoma or carcinoma Benamouzig et al, 2003;Sandler et al, 2003). These results have been confirmed in Asian patients as well (Ishikawa et al, 2014).…”
Section: Evolving Role Of Nsaids In Colon Cancer Preventionsupporting
confidence: 66%
“…Although the dose of aspirin and other aspects of these RCTs varied, the efficacy of aspirin was essentially consistent, providing a modest 17-35% reduction in risk of recurrent adenoma or carcinoma Benamouzig et al, 2003;Sandler et al, 2003). These results have been confirmed in Asian patients as well (Ishikawa et al, 2014).…”
Section: Evolving Role Of Nsaids In Colon Cancer Preventionsupporting
confidence: 66%
“…Human/laboratory studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] also suggested that n-3 PUFAs (or omega-3 PUFAs), including alpha-linolenic acid (ALA) and long-chain n-3 PUFAs (LC n-3 PUFAs) (eicosapentaenoic acid [EPA], docosapentaenoic acid [DPA], and docosahexaenoic acid [DHA]) seem to act as anti-tumor promoters in CRC carcinogenesis, like non-steroidal anti-inflammatory drugs (NSAIDs), including aspirin [29][30][31][32][33][34][35][36][37][38]. On the other hand, n-6 PUFAs (or omega-6 PUFAs, mainly linoleic acid (LA)) may act as tumor promoters, because they are upstream chemicals of n-6 family leukotrienes, thromboxanes and prostaglandins, which are catalyzed by lipoxygenase (LOX) and cyclooxygenase (COX) isoenzymes [39][40][41][42][43].…”
mentioning
confidence: 99%
“…A large collection of observational epidemiological studies [155][156][157][158], long-term follow-up for cancer of randomised primary prevention [159] or cardiovascular [160,161] trials, randomised trials on colon adenoma recurrence [162][163][164][165][166], and randomised trials in patients with hereditary colorectal cancer syndromes [167,168] have established that use of aspirin or other NSAIDs reduce the risk of colorectal neoplasia and cancer. There is also substantial evidence to suggest that use of aspirin or non-aspirin NSAIDs may protect against upper gastrointestinal cancers, including oesophageal and gastric cancer [158,[169][170][171][172].…”
Section: Aspirin and Other Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%